Who determines the trade-offs between agricultural production and environmental quality? An evolutionary perspective from rural eastern China. Issue 5 (3rd September 2019) - Dearing, John A.; Zhang, Ke; Cao, Weidong; Dawson, Terence P.; McKay, David Armstrong; Sillitoe, Paul; Treves, Richard; Yang, Xiangdong
ABSTRACT: We explore the evolutionary nature of interactions between government policy, farm decision-making and ecosystem services in Shucheng County, Anhui Province, 1950–2015. Analyses of ecological, social and economic trends are complemented by interviews with local farmers. Since the Household Responsibility System started in 1980, there has been a trade-off between rising levels of provisioning services and falling levels of regulating services with evidence that critical thresholds have been passed for water quality. Using a Framework for Ecosystem Service Provision, we argue that farmers have acted only as ecosystem service providers and have not influenced the policies that have brought about the trade-offs. Over the period, ecological degradation is best described as an example of 'creeping normalcy' where cumulative conventional actions by individual farmers produce unsustainable losses in regulating services. The Chinese government should act to balance the various ecosystem services through valuation and national policy. In this respect, there is a need for agencies that can provide place-based advice to farmers that will allow them to maintain productivity levels while pursuing restorative actions. Even with new policies, the draw of urban employment, high production costs and an ageing population threaten the viability of farming in these marginal agricultural areas.